The Institution of a Standardized Investigation Protocol for Sudden Infant Death in the Eastern Metropole, Cape Town, South Africa1, 2, 3. Issue 6 (27th September 2016) - Dempers, Johan J.; Coldrey, Jean; Burger, Elsie H.; Thompson, Vonita; Wadee, Shabbir A.; Odendaal, Hein J.; Sens, Mary Ann; Randall, Brad B.; Folkerth, Rebecca D.; Kinney, Hannah C.; ,
Abstract: The rate for the sudden infant death syndrome (SIDS) in Cape Town, South Africa, is estimated to be among the highest in the world (3.41/1000 live births). In several of these areas, including those of extreme poverty, only sporadic, nonstandardized infant autopsy, and death scene investigation (DSI) occurred. In this report, we detail a feasibility project comprising 18 autopsied infants with sudden and unexpected death whose causes of death were adjudicated according to the 1991 NICHD definitions (SIDS, n = 7; known cause of death, n = 7; and unclassified, n = 4). We instituted a standardized autopsy and infant DSI through a collaborative effort of local forensic pathology officers and clinical providers. The high standard of forensic investigation met international standards, identified preventable disease, and allowed for incorporation of research. We conclude that an effective infant autopsy and DSI protocol can be established in areas with both high sudden unexpected infant death, and elsewhere. (SUID)/SIDS risk and infrastructure challenges.